Penerapan Ciri Khas Arsitektur Melayu Pada Fasad Bangunan Kontemporer Di Kota Pekanbaru (Kasus Perkantoran Pemerintahan Di Tenayan Raya) - Fadli Rahman; Harry Kurniawan (Journal of Architectural Design and Development (JAD), 2021)
Pekanbaru City is the capital of Riau Province which has a majority of the population of Malay ethnicity. In maintaining its cultural characteristics, in the city of Pekanbaru there are many contemporary buildings that have the implementation of Malay characteristics on the facades of the buildings, which one is the object of this research, government offices in Tenayan Raya and Balai Payung Sekaki buildings, because the culture in an area is not only can be seen on thel Traditional House building, but other buildings must also be able to reflect regional characteristics such as a regional government office building which is one of the markers of an area. However, the application of Malay architecture must be done as well as possible so that there is no mistake because it can change the meaning contained in each characteristic feature of Malay architecture, meybe on roof components, ornaments or others. Misunderstanding or ignorance of a role in building also has a fatal impact on these formations. Although in plain view, these forms seem beautiful to feel, but philosophically and the meaning can be wrong. This research will be conducted with a descriptive approach to interpret an existing condition with a related theoretical basis to see the implementation of Malay architecture on the facades of contemporary buildings in Pekanbaru City. The entire implementation of Malay in buildings in the Tenayan Office area can be categorized as quite good in terms of authenticity because all the roofs and ornamental designs have the same motifs as the original motifs in traditional Malay buildings. The technique of applying ornament to the object of this research also varies, some are done by means of Stilation, Distortion or Repetition. However, he could not find any ornamental motifs that were applied using Decoration techniques.